Effect of Sn addition on mechanical properties of zinc-based alloy - Md Azizan, Farihan; Purwanto, Hadi; Mustafa, Mohd Yusry (Trans Tech Publications, Switzerland, 2012)
Zinc-based alloy is developed as an alternative alloy for giftware material. However, zinc alloy has limitation such as its mechanical properties. Therefore, modifying the properties of zinc based alloy is needed to use it for giftware material. The effect of adding Sn on the mechanical properties and fractography of Zn alloys are investigated. The results indicate that adding 15 wt.% of Sn has significant effect on the improving of tensile strength and elongation of the zinc based alloy due to the formation of AgSn phase. The fracture surface of the tensile test specimen showed a mixed mode of fracture exhibiting ductile failure and brittle failure. Alloy with Sn content up to 15 % tends to have more ductile failure then the brittle one. The alloys of Zn-0.50Ag-15Sn have very good tensile strength and elongation, which are better than Zn-0.50Ag-1Sn and Zn-0.50Ag-7Sn alloys.